Public Investment, Private Investment, and Labor Productivity in Nepal: A Cointegration and VECM Analysis - Chamlagai, Pranick Raj; Ramirez, Miguel D. (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The main objective of this paper is to analyze the impact of public and private investment on labor productivity in Nepal using time series data from 1991-2021. By employing the Zivot-Andrews single break unit root test and Johansen cointegration analysis, a long-run stable relationship is found among public investment, private investment, and labor productivity. A VECM model is estimated to find that both public and private investment have a positive impact on labor productivity with a more significant and strong impact coming from the private investment in the long run. The nature of labor productivity and public investment is found to be endogenous and that of private investment is found to be weakly exogenous. Additionally, a Granger Causality Test is performed and the result shows that labor productivity and private investment cause public investment. To test the causation from public investment to labor productivity, a Pairwise Granger Causality Test is done and it is found that public investment causes labor productivity only at lags of 4 and 5 which confirms that public investment takes time to impact the labor market conditions. Policy implications are discussed.